An update on the pharmacological management of post-herpetic neuralgia and painful diabetic neuropathy - Zin, Che Suraya; Nissen, Lisa M.; Smith, Maree T.; O'Callaghan, James P; Moore, Brendan J (Springer International Publishing, 2008)
Neuropathic pain is a persistent pain condition that develops secondary to nerve injury. The two most common types of peripheral neuropathic pain are post-herpetic neuralgia (PHN) and painful diabetic neuropathy (PDN). Amitriptyline, nortriptyline, desipramine and imipramine are TCAs that have been shown to be effective for the symptomatic relief of PHN and PDN. Serotonin noradrenaline reuptake inhibitors (SNRIs) such as venlafaxine and duloxetine have been shown to be very promising for the treatment of PDN with fewer adverse effects than TCAs. Selective serotonin reuptake inhibitors (SSRIs) were shown in a number of studies to have some efficacy in relieving PDN-related pain, yet other studies of the SSRIs have demonstrated conflicting outcomes. Most of the older antiepileptic studies were performed in patients with PDN; consequently, little is known about the efficacy of these drugs in patients with PHN. Carbamazepine, phenytoin and valproic acid were shown to be effective in ameliorating PDN-related pain. Other antiepileptic agents, including lamotrigine, oxcarbazepine and topiramate, have demonstrated some beneficial effects for the treatment of PDN, although they were also found to be ineffective in some PDN studies. alpha2delta Ligands such as gabapentin and pregabalin have been proven to be effective for the treatment of PHN and PDN in a number of large placebo-controlled trials. These drugs are useful not only in relieving pain but also in improving quality of life. Although the use of opioids for the treatment of neuropathic pain is controversial, a number of studies support the efficacy and safety of opioids in the treatment of neuropathic pain. Of these, oxycodone and tramadol have been shown to be superior to placebo for the treatment of PHN and PDN. A number of small studies have shown that dextromethorphan was effective in patients with PDN but not in patients with PHN. Topical agents such as lidocaine 5% patches and topical capsaicin are useful in ameliorating pain in patients with PHN but these agents are unsatisfactory for use as a sole agent. Although a number of drug treatments are available for the symptomatic relief of neuropathic pain symptoms, these agents do not provide satisfactory relief in all patients. For these patients, other treatment alternatives such as combination drug therapy that produces pain relief via distinctly different mechanisms may be successful. The purpose of this review is to compare the efficacy and limitations of currently available pharmacological treatments for the symptomatic relief of PHN and PDN, and to discuss the potential of combination therapy in PHN and PDN.